Pelatihan Guru Pendidikan Khusus; Implementasi Learning Aids Simulator dalam Meningkatkan Kesiapan Kerja Vokasional Siswa Tunadaksa - Zinnurain Zinnurain; Mujiburrahman Mujiburrahman; Ani Endriani (Jurnal Dedikasi Madani, 2026)
Vocational work readiness is one of the important competencies that must be possessed by students with disabilities to support independence and job opportunities in the future. However, the vocational learning process in special schools still faces various obstacles, especially the limited use of learning media that can bridge abstract concepts into concrete learning experiences. This community service activity aims to enhance the capacity of special education teachers in designing and implementing the Learning Aids Simulator as a vocational learning medium for students with disabilities. The activity was conducted at SLBN 1 Mataram and SLBN 2 Mataram, involving 20 special education teachers. The implementation method consists of needs identification, training, media usage demonstration, implementation assistance, monitoring, and evaluation. The results of the activities show that teachers are able to understand the concept of the Learning Aids Simulator, develop simple media according to the characteristics of the students, and integrate the simulator into vocational learning. In addition, teachers reported an increase in student engagement during the practical learning process. This activity proves that the use of Learning Aids Simulator can be an innovative alternative in supporting the improvement of vocational learning quality for students with disabilities. This program is expected to be replicated in other special schools to expand the impact of vocational skills development for students with special needs. Kata Kunci :